MECHANISMS OF CULTURAL VALUES AND STUDENTS’ BEHAVIORAL PRIORITIES FORMING UNDER THE INFLUENCE OF CONVERGED MEDIA MATERIALS - V N Levina; S V Guskova (Rusistika (Moskva. Online), 2017)
The topicality of the study is determined by a high degree of influence of modern media to the world audience; the more suspectable to outside influence is a youth audience, in which the process of formation of outlook, position in life, priorities, ideals and values is dynamic. Objective of the work is an exploratory study of cultural values and behaviors of students, which are formed under the influence of converged media materials, as well as forecasting of the situation. To study the materials involved in convergent media. During the work with material there were some methods of the use: textual method, content analysis method, comparative benchmarking. Effect materials converging media on the youth audience determined by the method of attracting the focus group study conducted in 2016, taking into account gender-specific subjects. A comparison with the data obtained in other studies in which young people are involved as subjects. The study revealed that converged media have a greater potential than traditional one, in particular, it is established a high degree of their influence on the youth audience. The situation is predicted for the future development of cultural values and behaviors of students under the influence of the mass media.